Linguistic Code Mixing: A Study of an Australian YouTuber - Serliah Nur; Muh. Taufik; Sakina Al Munawara (Hasanuddin University, 2023)
Mixing one language to another languages in sociolinguistics is called code mixing. It happens in one of the Australian Youtuber, Damian Hoo, who currently living in Indonesia. Therefore, this research discussed about the types and functions of code mixing produced by Australian Youtuber, Damian Hoo, based on Hoffman’s (1991) theory. This research applied descriptive qualitative method. In collecting the data, the researchers applied documentation method. The result of the research revealed that there are two types produced by Damian Hoo in his YouTube channel, namely intra-sentential code mixing with 55 data and involving a change of pronunciation with only 2 data. For the functions of code mixing, there are six functions of code mixing which are used by Damian Hoo, such as talking about a particular topic as the highest number for function with 25 data, being emphatic about something with 10 data, interjection with 3 data, repetition used for clarification with 6 data, intention of clarifying the speech content for the interlocutor with 12 data, and the last expressing group identity with only 1 data which makes this function is the less used function of code mixing. And the researchers did not find any data of the intra-lexical code mixing and function for quoting somebody else.